PENGARUH STRUKTUR MODAL TERHADAP DAYA SAING PASAR PRODUK: Studi Perusahaan di Bursa Efek Indonesia - Rushpaka, Bunga Nirwana Venda (LP2M Institut Teknologi dan Bisnis Asia Malang, 2020)
Capital structure affects the competitiveness of the company's products. Increasing quickly in leverage will make companies easier to have sufficiently profitable capital in increasing company size, increasing investment, and helping companies determine a dominant position in the market. The purpose of this study was to study the interaction of capital structure on the market competitiveness of products in companies in Indonesia which were listed on the Indonesia Stock Exchange (IDX) during 2014-2018. The methodology used in this study is quantitative using secondary data consisting of financial statements of companies listed on the IDX. A total of 77 samples of manufacturing companies with regression analysis, using SPSS software version 22. Capital structure is determined by leverage, while product market competitiveness is taken with the Hefindahl Hirschman Index (HHI). There are three control variables in this study, profitability, size, growth. The results of this study indicate a significant positive effect between capital structure and product market competitiveness in industries in Indonesia.